Frequency of Helicobacter Pylori Infection in Children presented with Recurrent Abdominal Pain in Northern part of Bangladesh - Ghosh, Uzzal Kumar; Md Imrul Kaes; Satabdi Ghosh; Mosammat Afroza Jinnat; Chandan Kumar Saha; Md Zulfikar Ali (KYAMC Journal, 2023)
Background: Abdominal pain is one of the common symptoms in hospital attended children. Recurrent abdominal pain also is a challenge to diagnosis. Although the most common etiology of recurrent abdominal pain is functional, organic treatable cause exclusion is justified. Peptic ulcer disease is one of the causes of recurrent abdominal pain; whereas association of Helicobacter Pylori is not so uncommon. Objective: To find out the frequency of H Pylori infection in children presented with recurrent abdominal pain. Materials and methods: A cross sectional was study done in Khwaja Yunus Ali Medical College located in northern part of Bangladesh. One hundred eight recurrent abdominal pain (RAP) cases were included in our study. Along with the other investigations ICT for H Pylori was sent to find out the etiology of recurrent abdominal pain in children attending in outpatient and inpatient department of pediatrics. RAP were our study population (N). H Pylori positive & H Pylori negative test results were included in data sheet. Demographic characteristics were noted among the H pylori positive cases (n) including age, sex and socioeconomic condition. Data were analyzed in Microsoft Excel. Results: Among the 108 RAP cases H Pylori infection were found 37(34.25%) by diagnostic test ICT for H. pylori. Out of 37(34.26%) H pylori positive children 21(56.76%) were male 16(43.24%) were female. Children aged 7 to 9 year constituted 6(16.21%), 10 to12 year 12(32.43%), 13 to 15 year 19(51.36%). Twenty six (70.27%) belonged to rural area and 11 (29.73%) belonged to urban area. Low income family 28(75.68%), medium income family 5(13.51%) and high income family were found 4(10.81%). Conclusion: About thirty five percent H Pylori infection are found in children presented with recurrent abdominal pain in northern part of Bangladesh among the seven to fifteen year child. KYAMC Journal Vol. 14, No. 01, April 2023: 04-06